Distribuição espaço temporal de sistemas precipitantes e relâmpagos no norte do estado do Pará e estado do Amapá - MORAES, Jacqueline Belo (2019)
This study analyzed 15 years of data on spatial and temporal distribution of lightning, precipitation systems and their characteristics such as brightness temperature and height of precipitating systems sampled by the satellite Tropical Rainfall Measuring Mission (TRMM) sensors through the Lightning Imaging Sensor (LIS), Precipitation Radar (PR) and TRMM Microwave Imager (TMI) data were used for the years 12/1997 a12/12012 and delimited areas selected between 53 ° W to 47 ° E longitude and 3 ° N to 3 ° S latitude and subsequently selected four subareas(I- Region-53W _50W 0N _3N, Region II-50W_47W 0N_3N, III- Region - 53W_50W 0N_3S and IV- Region - 53W_50W3S_0N). The present work aims to make a analysis of the distribution of lightning in some areas of the Amazon region and surroundings, analyze occurrences of lightning in the regions under study, identifying the months of larger samples, the most affected areas and the influence of precipitation systems (PFS) in the occurrence of lightning. The classification systems followed the methodology of Nesbitt et al. (2000).With respect to the systems that were checked were ALLPFS systems that contributed to the volume of precipitation, followed by MCS. Results also showed that the regions of highest occurrences were the regions to the south (IV- 53W_50W 3S_0N) and (III- 53W_50W 0N_3S) having(14220 and 12337 events), respectively; area covering the South of Pará, in Belém and Marajó, and the MCS and WICE were the main contributors to the production of rays over these regions.